Multi-Domain Assessment of Thermomechanical Recycling Based on Bio-Based and Petroleum-Based Additively Manufactured Components - Niko Nagengast; Nicolas Mandel; Christian Bay; Frank Döpper; Christian Neuber; Hans-Werner Schmidt; Clara Usma-Mansfield; Franz Konstantin Fuss (Recycling)
The surge in global population growth and the escalating demand for social and economic prosperity present formidable challenges in the 21st century. However, asserting the sustainability of some ecological impact reduction initiatives, such as recycling, requires a comprehensive evaluation within various domains, including performance, ecology, and economics, and contemporary advancements in integrating quantitative assessments of material and manufacturing properties, coupled with mathematical decision-making approaches, contribute to mitigating subjectivity in determining the efficiency of recycling. This paper implements a robust multi-criteria decision-making (MCDM) approach to address the complexities of recycling, validating its implementation and effectiveness through a case study. The focus is set on the application of bio-based polylactic acid (PLA) and petroleum-based polypropylene (PP) additively manufactured (AM) parts produced through Fused Filament Fabrication (an approach to ecology/performance domains). The work introduces a cost analysis focusing on calculating thermomechanical recycling within the economic domain. The well-known Analytical Hierarchical Process (AHP) provides a structured framework for decision-making (the ecological impact domain) with the focus being on application. The assessment or recycling viability, encompassing AHP calculations, preprocessing, and supplementary tools, is provided by developing an open-source software tool for practitioners in the field of material science and manufacturing. The results indicate a preference for industrial-scaled recycling over virgin or lab-recycled manufacturing, particularly for petroleum-based polypropylene. The versatility and simple utilization of the software tool allow seamless integration for diverse use cases involving different materials and processes.